Aproveitamento de resíduos de frutas da Amazônia no processo de bioconversão por fungos basidiomicetos para a produção de ração animal - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Brazil is the third largest producer of fruit in the world and the leader in the production of tropical fruits, reaching approximately 44 million tons of fruits per year, being much processed industrially, generating tons of waste that are normally discarded in nature. The Basidiomycete fungi are lignocellulosic, that is, they have the ability to degrade complex compounds such as cellulose and lignin; these fungi are grown on substrates based on residues that, at the end of their cultivation, present high nutritional value similar to the fruiting body. These post-culture substrates, also called spent substrates, are usually discarded or used as organic fertilizer. This work had as objective to produce an animal feed, from the fungal substrate. The first step was the collection, nutritional and microbiological analysis of fruit pulp residues according to the greater local availability and harvest period. After nutritional analysis, the açaí residue was selected, which, together with calcium carbonate, was used as substrate for Pleurotus ostreatus and Lentinula edodes. From the cultivation, the two-stage mushroom substrates at the initiations colonization and post-cultivation were tested as feed for broiler chickens by digestibility analysis using the total excreta collection method, with crude energy, metabolizable and corrected nitrogen energy, as well as haematological and parasitological analysis of the birds. From these results, the substrate of açaí colonized by Pleurotus ostreatus was selected to perform performance analysis, carcass characteristics, absolute and relative weights of organs, chemical composition of noble cuts and height of intestinal villi of broiler chickens in stages of development. A total of 360 non-sexed Cobb commercial broiler chicks were used in two stages of development, growth phase (21 to 33 days) and final phase (33 to 42 days). The experimental design will be completely randomized with treatments in 5 x 2 factorial arrangement (diets and 2 stages of development). The diets were formulated with different concentrations of the selected substrates after digestibility assay (0%, 3%, 6%, 9% and 12%), and were supplied to six plots with 12 birds per plot. The results demonstrated the feasibility of using the substrate at an average level of 5% of inclusion, evidenced in the improvement of characteristics such as lower abdominal fat weight, higher protein content in the meat and lower lipid content, as well as evidence of benefits regarding immunity and health of animals. The histological analysis of the intestinal villi showed characteristics compatible with the consumption of fiber-rich diets, with the heights decreasing with the increase of the inclusion level of the substrate. Thus, a feed supplemented with an additive of lower cost and high environmental value was produced, the low nutritional content of the residue being modified by the cultivation of basidiomycete fungi that performed the bioconversion of complex compounds, making them available to be absorbed by the organism animal and adding characteristics similar to the mycelium present in the substrate.
Keywords: Resíduos; Frutas tropicais; Rações; Reaproveitamento (Sobras, refugos, etc.); Fungos; Basidiomicetos; CIÊNCIAS BIOLÓGICAS